2016
DOI: 10.1182/blood-2015-09-666214
|View full text |Cite
|
Sign up to set email alerts
|

The impact of multiple low-level BCR-ABL1 mutations on response to ponatinib

Abstract: The third-generation tyrosine kinase inhibitor (TKI) ponatinib shows activity against all common BCR-ABL1 single mutants, including the highly resistant BCR-ABL1-T315I mutant, improving outcome for patients with refractory chronic myeloid leukemia (CML). However, responses are variable, and causal baseline factors have not been well-studied. The type and number of low-level BCR-ABL1 mutations present after imatinib resistance has prognostic significance for subsequent treatment with nilotinib or dasatinib as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 29 publications
(54 reference statements)
5
47
0
2
Order By: Relevance
“…1 Furthermore, ponatinib might be superior to other 2G-TKIs in terms of its efficacy in patients with ABL1 mutations, in addition to those carrying T315I. 9 This is consistent with the observation that patients failing ponatinib therapy are unlikely to respond to subsequent TKI. 10 The observations from the current study are encouraging regarding the prospect of lower dose ponatinib (15 mg daily) being as effective as the standard dose (45 mg daily).…”
supporting
confidence: 64%
“…1 Furthermore, ponatinib might be superior to other 2G-TKIs in terms of its efficacy in patients with ABL1 mutations, in addition to those carrying T315I. 9 This is consistent with the observation that patients failing ponatinib therapy are unlikely to respond to subsequent TKI. 10 The observations from the current study are encouraging regarding the prospect of lower dose ponatinib (15 mg daily) being as effective as the standard dose (45 mg daily).…”
supporting
confidence: 64%
“…26 The presence of compound mutations describe poor-risk group of chronic phase CML patients, with increased chances of disease progression and acquiring resistance with suboptimal response to second generation TKIs. 16 However, it is expected that each of compound mutant clone retains its own sensitivity against given treatment. 5 Presence of 2 or more mutations in ABL kinase domain impair the binding of Imatinib, resulting in suboptimal treatment outcome and progression of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Though BCR-ABL compound mutations have been found to be responsible for causing resistance to all tyrosine kinase inhibitors (TKIs) currently in clinical practice 10-15 including ponatinib, 16,17 reports about role of compound ABL mutations in CML progression are lacking. 5,9 In the present study, we studied BCR-ABL kinase domain mutations in imatinib sensitive patients of CML in CP, late CP, AP and BC of the disease using Sanger sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…44 Therefore, subclonal diversity could be an important prognostic marker of the capacity of leukemic cells to evolve TKI resistance. Interestingly, using the mass spectrometry sensitive mutation technique, Parker et al 45 demonstrated in chronic-and advancedphase patients treated with ponatinib in the PACE study that the association between multiple low-level mutations and poor outcome was not found with ponatinib therapy. Therefore, ponatinib may be beneficial for patients with multiple mutations after prior TKI.…”
Section: Molecular Monitoring: How Low Do You Need To Go?mentioning
confidence: 99%